Petroleum exploitation tensile cable based on high polymer material and production method thereof

By using bio-based polymer composite materials and multi-stage gradient blending process, the produced petroleum exploitation tensile cable solves the problems of environmental pollution and insufficient performance of traditional cable materials, and achieves high-performance, environmentally friendly and stable cable products.

CN119592028APending Publication Date: 2025-03-11YANGZHOU TIANDI WIRE & CABLE CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411713879.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional petroleum exploitation tensile cable materials have problems such as environmental pollution, aging, cracking, and insufficient tensile strength and wear resistance, making it difficult to meet the strict needs of the petroleum exploitation industry.

Method used

Bio-based polymer composite materials are used as the insulating layer, combined with a variety of high-performance additives and multi-stage gradient blending processes to make petroleum mining tensile cables with excellent environmental protection and high performance.

Benefits of technology

It improves the environmental protection and biodegradability of the cable, enhances tensile strength and stability, is suitable for harsh oil extraction environments, extends service life and improves safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592028A_ABST
    Figure CN119592028A_ABST
Patent Text Reader

Abstract

The invention discloses an oil exploitation tensile cable based on a high polymer material and a production method thereof, and relates to the technical field of cables, the cable comprises a conductor and an insulating layer wrapping the conductor, the insulating layer is made of a bio-based high polymer composite material, the bio-based polymer composite material comprises the following components in parts by weight: 50-70 parts of a bio-based polymer matrix and 20-30 parts of reinforced fibers. The bio-based polymer composite material is adopted as an insulating layer of the tensile cable for oil exploitation, so that the environmental protection performance and biodegradability of the tensile cable for oil exploitation are improved; the material is composed of polylactic acid, a polyhydroxyalkanoate bio-based polymer matrix and a plurality of high-performance additives, conventional synthetic fiber reinforcement is included, natural fibers are introduced to be compounded with a bio-based polymer material, and the unique fiber structure and surface performance of the material can form good interaction with bio-based polymers, so that the high-performance composite material is obtained. Therefore, the strength and toughness of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cables, in particular to a high polymer material-based oil extraction tensile cable and a production method thereof. Background Art

[0002] In the process of oil extraction, tensile cables play a vital role. They not only need to withstand huge tensile forces, but also need to maintain stable performance under harsh environmental conditions. With the advancement of science and technology and the improvement of environmental awareness, the requirements for cable materials are becoming increasingly stringent. In recent years, polymer materials have been widely used in the field of cable manufacturing due to their excellent physical properties and processing properties. Especially in the selection of insulation layer materials, polymer materials have become a research hotspot.

[0003] In traditional technology, oil extraction tensile cables mostly use petroleum-based polymer materials as insulation layers. However, this material has many shortcomings. On the one hand, petroleum-based polymer materials are difficult to degrade, causing long-term pollution to the environment, which is not in line with current environmental protection concepts. On the other hand, these materials are prone to aging and cracking in extreme environments, resulting in degraded cable performance and even safety accidents. In addition, the tensile strength and wear resistance of traditional cable materials need to be improved to meet the growing needs of oil extraction.

[0004] Therefore, a polymer-based tensile-resistant cable for oil extraction and a production method thereof are developed to ensure the stability and reliability of the cable in harsh environments, providing a higher-quality and more environmentally friendly cable solution for the oil extraction industry. Summary of the Invention

[0005] The purpose of the present invention is to make up for the shortcomings of the existing technology and provide an oil extraction tensile cable based on polymer materials and a production method thereof. The cable uses bio-based polymer composite materials to make the insulation layer, has excellent environmental performance and biodegradability, and at the same time has good tensile strength and stability, and is suitable for harsh oil extraction environments. By precisely controlling the raw material ratio and adopting a multi-stage gradient blending process, uniform mixing of materials and high performance are achieved.

[0006] To solve the above technical problems, the present invention provides the following technical solutions: On the one hand, a polymer-based oil production tensile cable comprises a conductor and an insulating layer coated on the outside of the conductor, wherein the insulating layer is made of a bio-based polymer composite material, and the bio-based polymer composite material comprises, by weight, 50-70 parts of a bio-based polymer matrix, 20-30 parts of reinforcing fiber, 3-5 parts of an antioxidant, 2-3 parts of a lubricant, 5-10 parts of a flame retardant, and 1-3 parts of a fluorescent tracer; The bio-based polymer matrix is ​​polylactic acid and polyhydroxyalkanoate; The reinforcing fibers include carbon fibers, aramid fibers, basalt fibers and natural fibers; The antioxidant is antioxidant 1010, with an active ingredient content of ≥98% or triphenyl phosphite, with a purity of 95%-99%; The lubricant is zinc stearate with a particle size of 2-5 μm or polyethylene wax with a molecular weight of 3000-6000; The flame retardant is magnesium hydroxide with a particle size of 1-3 μm, aluminum hydroxide with a particle size of 2-4 μm or tricresyl phosphate with a purity of 90%-95%; The fluorescent tracer is an organic or inorganic compound with fluorescent properties and compatible with a bio-based polymer matrix. The organic compound is rhodamine or coumarin, and the inorganic compound is europium-doped strontium aluminate.

[0007] Furthermore, the weight average molecular weight of the polylactic acid in the bio-based polymer matrix is ​​100,000-200,000, the weight average molecular weight of the polyhydroxyalkanoate is 80,000-150,000, and the mass ratio of the polylactic acid to the polyhydroxyalkanoate is 3:2-2:1.

[0008] Furthermore, the carbon fiber in the reinforcing fiber has a diameter of 5-10 μm, a length of 3-8 mm, a tensile strength of 3000-5000 MPa, and an elastic modulus of 200-400 GPa; the aramid fiber has a diameter of 10-15 μm, a length of 2-6 mm, and a tensile strength of 2500-4000 MPa; and the basalt fiber has a diameter of 8-12 μm, a length of 3-7 mm, and a tensile strength of 2000-3500 MPa.

[0009] Furthermore, the natural fibers in the reinforcing fibers are flax fibers and sisal fibers, which account for 20%-40% of the total reinforcing fibers.

[0010] Furthermore, the fluorescent tracer comprises rhodamine with a purity of 95%-99%, coumarin 343 with a purity of 90%-98%, and europium-doped strontium aluminate with a particle size of 5-10 μm.

[0011] On the other hand, a method for producing a tensile cable for oil production based on a polymer material, the specific steps of the production method are: S100, raw material preparation and preliminary mixing: weighing the raw materials according to the weight ratio of the oil extraction tensile cable based on polymer materials according to claims 1 to 5 above, adding the bio-based polymer matrix, antioxidant, lubricant, flame retardant and fluorescent tracer into a high-speed mixer, and mixing at 50-80° C. and 500-800 rpm for 10-20 minutes to obtain a premix; S200, reinforcing fiber addition and mixing: adding the reinforcing fiber to the premix and mixing in a high-speed mixer for 5-10 minutes at a mixer speed of 300-600 rpm; S300, multi-stage gradient blending: The mixed materials are processed using a multi-stage gradient blending process, with preliminary mixing at a low temperature and low speed stage, gradual mixing and outward diffusion of the premix core and the remaining polymer materials at a medium temperature and medium speed stage, and intensive mixing at a high temperature and high speed stage to obtain the processed bio-based polymer composite material; S400, twin-screw extrusion granulation: The treated bio-based polymer composite material is added to the twin-screw extruder, the screw temperature is set to 150-200℃, the screw speed is 200-300 rpm, the extruded material is cooled in a water tank with the water temperature controlled at 20-30℃, and after cooling, it is cut into pellets with a particle size of 3-5mm by a pelletizer; S500, cable overmolding: Bio-based polymer composite pellets are overmolded onto the conductor through an extruder at an extrusion temperature of 180-220°C and an extrusion pressure of 10-20 MPa. After traction, cooling, and winding, an oil extraction tensile cable is obtained.

[0012] Furthermore, in the S300, the temperature of the low-temperature and low-speed stage in the multi-stage gradient blending is set to 80-120° C., the rotation speed is 100-200 rpm, and the mixing time is 5-8 minutes.

[0013] Furthermore, in the S300, the medium-temperature and medium-speed stage in the multi-stage gradient blending is set at a temperature of 130-160° C., a rotation speed of 250-350 rpm, and a time of 8-12 minutes.

[0014] Furthermore, the temperature of the high-temperature and high-speed stage in the multi-stage gradient blending in S300 is set to 170-200° C., the rotation speed is 400-500 rpm, and the time is 3-5 minutes.

[0015] Furthermore, in the S500, the pulling speed in the cable overmolding is set to 5-10 m / min, the cooling is done by air cooling with an air temperature of 15-25° C., and the winding tension is controlled at 50-100N.

[0016] Compared with the existing technology, the oil extraction tensile cable based on polymer materials and the production method thereof have the following beneficial effects: 1. The present invention improves the environmental performance and biodegradability of oil extraction tensile cables by using bio-based polymer composite materials as the insulation layer of the oil extraction tensile cable. This material is composed of a polylactic acid, polyhydroxyalkanoate bio-based polymer matrix and a variety of high-performance additives. It not only includes conventional synthetic fiber reinforcements, but also introduces natural fibers and bio-based polymer materials. Natural fibers are widely available, renewable and relatively low in cost. Their unique fiber structure and surface properties can form a good interaction with bio-based polymers, thereby improving the strength and toughness of the material.

[0017] 2. The present invention ensures the excellent performance and stability of oil extraction tensile cables through the designed raw material ratio and production process. In terms of raw material selection, the present invention combines a variety of high-performance additives, such as reinforcing fibers, antioxidants, lubricants, flame retardants and fluorescent tracers. The synergistic effect of these additives makes the cable have higher strength, better wear resistance, longer service life and better safety performance. In terms of production process, the present invention adopts multi-stage gradient blending technology to ensure uniform mixing and full reaction between the components, thereby improving the overall performance and stability of the cable. In addition, by precisely controlling parameters such as extrusion temperature and pressure, the present invention also achieves precise control of cable overmolding, further improving the quality and reliability of the cable.

[0018] Other advantages, objects and features of the present invention will be described in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be learned from the practice of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort.

[0020] Figure 1 The present invention is a flow chart of a polymer material-based oil extraction tensile cable and its production method. DETAILED DESCRIPTION

[0021] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0022] Comparative Example 1: During oil well extraction operations on an offshore oil platform, a tensile cable is required that can withstand high temperatures (up to 150°C), high pressures (approximately 50 MPa), and highly corrosive media (including hydrogen sulfide and salt water). Furthermore, to facilitate routine maintenance and troubleshooting, the cable should ideally be detectable.

[0023] First, materials are prepared according to the formula of the present invention, including 42 parts of polylactic acid (weight-average molecular weight of 150,000) and 28 parts of polyhydroxyalkanoate (weight-average molecular weight of 100,000); 25 parts of reinforcing fibers, including 10 parts of carbon fiber (diameter 7 μm, length 5 mm, tensile strength 4000 MPa, elastic modulus 300 GPa), 5 parts of aramid fiber (diameter 12 μm, length 3 mm, tensile strength 3500 MPa), 3 parts of basalt fiber (diameter 10 μm, length 4 mm, tensile strength 2500 MPa) and 7 parts of flax fiber (length 4 mm); 4 parts of antioxidant 1010 (active ingredient content 99%); 2.5 parts of zinc stearate (particle size 3 μm); 8 parts of magnesium hydroxide (particle size 2 μm); and 2 parts of fluorescent tracer rhodamine B (purity 98%).

[0024] Then proceed to production: S100: Raw material preparation and preliminary mixing: Add the above-weighed bio-based polymer matrix, antioxidant, lubricant, flame retardant and fluorescent tracer into a high-speed mixer, set the temperature to 65°C and the speed to 650 rpm, and mix for 15 minutes to obtain a premix.

[0025] S200: Adding and mixing reinforcing fibers: Add reinforcing fibers to the premix and mix in a high-speed mixer at 450 rpm for 8 minutes.

[0026] S300: Multi-stage gradient blending: In the low-temperature and low-speed stage, the temperature was set to 105°C and the speed was 150 rpm for 6 minutes to evenly disperse the additives in part of the polymer material to form a premix core; In the medium temperature and medium speed stage, the temperature was adjusted to 145°C and the speed was 300 rpm for 10 minutes to allow the premix core and the remaining polymer materials to gradually mix and diffuse outward; In the high-temperature and high-speed stage, the temperature was set at 185°C, the speed was 450 rpm, and mixing was performed for 4 minutes to ensure overall uniformity, thereby obtaining the processed bio-based polymer composite material.

[0027] S400: Twin-screw extrusion granulation: The treated bio-based polymer composite material is placed into a twin-screw extruder, the screw temperature is set to 180°C, the screw speed is 250 rpm, and after extrusion, it is cooled in a water tank at a water temperature of 25°C, and then cut into pellets with a particle size of 4 mm using a pelletizer.

[0028] S500: Cable overmolding: Use pellets to overmold the copper conductor through an extruder, with an extrusion temperature of 200°C, an extrusion pressure of 15 MPa, a pulling speed of 8 m / min, air cooling at 20°C, and a winding tension of 80 N to finally obtain an oil extraction tensile cable.

[0029] After testing, its tensile strength reaches over 450MPa. In the tensile test simulating the oil extraction environment, the cable can withstand a tensile force of up to 5000N without breaking, which has significant advantages over traditional petroleum-based polymer cable materials.

[0030] Example 1: In an operation at a certain onshore oil well, the environmental requirements are similar to those before. The cables must be able to withstand high temperatures (up to 150°C), high pressures (approximately 50 MPa), and highly corrosive media (including hydrogen sulfide and brine). Furthermore, the cables must be detectable.

[0031] Prepare the materials: take 50 parts of polylactic acid (weight-average molecular weight of 100,000) and 20 parts of polyhydroxyalkanoate (weight-average molecular weight of 80,000) as the bio-based polymer matrix; 25 parts of reinforcing fibers, including 10 parts of carbon fiber (diameter 7μm, length 5mm, tensile strength 4000MPa, elastic modulus 300GPa), 5 parts of aramid fiber (diameter 12μm, length 3mm, tensile strength 3500MPa), 3 parts of basalt fiber (diameter 10μm, length 4mm, tensile strength 2500MPa) and 7 parts of flax fiber (length 4mm); 4 parts of antioxidant 1010 (active ingredient content 99%); 2.5 parts of zinc stearate (particle size 3μm); 8 parts of magnesium hydroxide (particle size 2μm); 2 parts of fluorescent tracer rhodamine B (purity 98%).

[0032] Production steps: S100: Raw material preparation and preliminary mixing: Add the above raw materials into a high-speed mixer at a temperature of 65° C. and a speed of 650 rpm, and mix for 15 minutes to obtain a premix.

[0033] S200: Reinforcement fiber addition and mixing: Add the reinforcement fiber to the premix and mix at 450 rpm for 8 minutes.

[0034] S300: Multi-stage gradient blending: Low temperature and low speed stage: 105°C, 150 rpm, mixing for 6 minutes; Medium temperature and medium speed stage, 145°C, 300 rpm, mixing for 10 minutes; In the high temperature and high speed stage, the mixing speed was 185° C. and 450 rpm for 4 minutes to obtain the processed composite material.

[0035] S400: Twin-screw extrusion granulation: put into twin-screw extruder, screw temperature 180℃, speed 250 rpm, cool in 25℃ water tank and then cut into pellets, particle size 4mm.

[0036] S500: Cable overmolding: Copper conductor coated with pellets, extrusion temperature 200℃, pressure 15MPa, pulling speed 8m / min, air cooling 20℃, winding tension 80N.

[0037] After testing, its tensile strength reaches more than 420MPa. In the tensile test simulating the oil extraction environment, it can withstand a tensile force of 4800N without breaking.

[0038] Example 2: During oil well operations in a desert oil production area, operators face high temperatures (up to 150°C), high pressure (approximately 50 MPa), a highly corrosive environment, and high cable detectability requirements.

[0039] Material preparation: The bio-based polymer matrix is ​​35 parts of polylactic acid (weight-average molecular weight 200,000) and 35 parts of polyhydroxyalkanoate (weight-average molecular weight 150,000); 25 parts of reinforcing fiber (composition is the same as before); 4 parts of antioxidant 1010 (active ingredient content 99%); 2.5 parts of zinc stearate (particle size 3μm); 8 parts of magnesium hydroxide (particle size 2μm); 2 parts of fluorescent tracer rhodamine B (purity 98%).

[0040] Production process: S100: Mix the raw materials at 65°C and 650 rpm for 15 minutes to obtain a premix.

[0041] S200: Add fiber and mix, 450 rpm, 8 minutes.

[0042] S300: Multi-stage gradient blending: Low temperature and low speed: 105°C, 150 rpm, 6 minutes; Medium temperature and medium speed: 145°C, 300 rpm, 10 minutes; High temperature and high speed, 185℃, 450 rpm, 4 minutes, to obtain a composite material.

[0043] S400: twin-screw extrusion, 180℃, 250 rpm, cooling in 25℃ water tank, pelletizing, particle size 4mm.

[0044] S500: overmolding, 200°C, 15 MPa, pulling 8 m / min, air cooling 20°C, winding 80N.

[0045] After testing, the tensile strength is over 460MPa, and the simulated tensile test can withstand a tensile force of 5200N without breaking.

[0046] Example 3: In oil well operations in a certain mountainous area, the environmental conditions are high temperature (up to 150°C), high pressure (pressure about 50MPa), highly corrosive media, and the cable needs to be detectable.

[0047] Take the bio-based polymer matrix: 38 parts of polylactic acid (weight average molecular weight 180,000), 32 parts of polyhydroxyalkanoate (weight average molecular weight 120,000); 25 parts of reinforcing fiber (composition unchanged); 4 parts of antioxidant 1010 (active ingredient content 99%); 2.5 parts of zinc stearate (particle size 3μm); 8 parts of magnesium hydroxide (particle size 2μm); 2 parts of fluorescent tracer rhodamine B (purity 98%).

[0048] The production steps are as follows: S100: Mix the raw materials at 65°C and 650 rpm for 15 minutes to obtain a premix.

[0049] S200: adding reinforcing fibers, 450 rpm, 8 minutes.

[0050] S300: Multi-stage gradient blending: Low temperature and low speed: 105°C, 150 rpm, 6 minutes; Medium temperature and medium speed: 145°C, 300 rpm, 10 minutes; High temperature and high speed, 185℃, 450 rpm, 4 minutes, to make composite materials.

[0051] S400: Twin-screw extrusion granulation, 180℃, 250 rpm, cooling and pelletizing in a 25℃ water tank, particle size 4mm.

[0052] S500: Coated copper conductor, 200°C, 15 MPa, pulling 8 m / min, air cooling 20°C, winding 80N.

[0053] After testing, its tensile strength reaches more than 440MPa, and it can withstand a tensile force of 5000N without breaking in a simulated oil extraction tensile test.

[0054] Example 4: In a shallow-water oil extraction operation, the environment requires adaptation to underground high temperatures (up to 150°C), high pressure (approximately 50 MPa), highly corrosive media, and the cable must be detectable.

[0055] Material preparation: The bio-based polymer matrix includes 42 parts of polylactic acid (weight-average molecular weight 150,000) and 28 parts of polyhydroxyalkanoate (weight-average molecular weight 100,000); 25 parts of reinforcing fibers, including 15 parts of carbon fiber (diameter 7 μm, length 5 mm, tensile strength 4000 MPa, elastic modulus 300 GPa), 3 parts of aramid fiber (diameter 12 μm, length 3 mm, tensile strength 3500 MPa), 2 parts of basalt fiber (diameter 10 μm, length 4 mm, tensile strength 2500 MPa) and 5 parts of flax fiber (length 4 mm); 4 parts of antioxidant 1010 (active ingredient content 99%); 2.5 parts of zinc stearate (particle size 3 μm); 8 parts of magnesium hydroxide (particle size 2 μm); 2 parts of fluorescent tracer rhodamine B (purity 98%).

[0056] Production steps: S100: Raw material preparation and preliminary mixing: Add the raw materials into a high-speed mixer at 65°C and 650 rpm and mix for 15 minutes to obtain a premix.

[0057] S200: Reinforcement fiber addition and mixing: Add the reinforcement fiber to the premix and mix at 450 rpm for 8 minutes.

[0058] S300: Multi-stage gradient blending: Low temperature and low speed stage: 105°C, 150 rpm, mixing for 6 minutes; Medium temperature and medium speed stage, 145°C, 300 rpm, mixing for 10 minutes; In the high temperature and high speed stage, the mixing speed was 185° C. and 450 rpm for 4 minutes to obtain the processed composite material.

[0059] S400: Twin-screw extrusion granulation: put into a twin-screw extruder, screw temperature 180℃, screw speed 250 rpm, cool in a 25℃ water tank and then cut into pellets, particle size 4mm.

[0060] S500: Cable overmolding: Copper conductor coated with pellets, extrusion temperature 200℃, pressure 15MPa, pulling speed 8m / min, air cooling 20℃, winding tension 80N.

[0061] After testing, its tensile strength reaches more than 480MPa. In the tensile test simulating the oil extraction environment, it can withstand a tensile force of 5500N without breaking.

[0062] Embodiment 5: In a certain deep-sea oil extraction scenario, the system faces high underground temperatures (up to 150°C), high pressure (approximately 50 MPa), a highly corrosive environment, and requirements for cable detectability.

[0063] Prepare materials: The bio-based polymer matrix is ​​42 parts of polylactic acid (weight-average molecular weight 150,000) and 28 parts of polyhydroxyalkanoate (weight-average molecular weight 100,000); the reinforcing fibers are 25 parts, including 8 parts of carbon fiber (diameter 7μm, length 5mm, tensile strength 4000MPa, elastic modulus 300GPa), 8 parts of aramid fiber (diameter 12μm, length 3mm, tensile strength 3500MPa), 4 parts of basalt fiber (diameter 10μm, length 4mm, tensile strength 2500MPa) and 5 parts of flax fiber (length 4mm); 4 parts of antioxidant 1010 (active ingredient content 99%); 2.5 parts of zinc stearate (particle size 3μm); 8 parts of magnesium hydroxide (particle size 2μm); 2 parts of fluorescent tracer rhodamine B (purity 98%).

[0064] Production process: S100: Mix the raw materials at 65°C and 650 rpm for 15 minutes to obtain a premix.

[0065] S200: Add fiber and mix, 450 rpm, 8 minutes.

[0066] S300: Multi-stage gradient blending: Low temperature and low speed: 105°C, 150 rpm, 6 minutes; Medium temperature and medium speed: 145°C, 300 rpm, 10 minutes; High temperature and high speed, 185℃, 450 rpm, 4 minutes, to obtain a composite material.

[0067] S400: twin-screw extrusion, 180℃, 250 rpm, cooling in 25℃ water tank, pelletizing, particle size 4mm.

[0068] S500: overmolding, 200°C, 15 MPa, pulling 8 m / min, air cooling 20°C, winding 80N.

[0069] After testing, the tensile strength is over 460MPa, and the simulated tensile test can withstand a tensile force of 5300N without breaking.

[0070] Example 6: In a certain saline-alkali oil well, the environment is high temperature (up to 150°C), high pressure (pressure about 50MPa), highly corrosive medium and requires cable detection.

[0071] Take the bio-based polymer matrix: 42 parts of polylactic acid (weight-average molecular weight 150,000), 28 parts of polyhydroxyalkanoate (weight-average molecular weight 100,000); 25 parts of reinforcing fibers, including 12 parts of carbon fiber (diameter 7μm, length 5mm, tensile strength 4000MPa, elastic modulus 300GPa), 6 parts of aramid fiber (diameter 12μm, length 3mm, tensile strength 3500MPa), 2 parts of basalt fiber (diameter 10μm, length 4mm, tensile strength 2500MPa) and 5 parts of flax fiber (length 4mm); 4 parts of antioxidant 1010 (active ingredient content 99%); 2.5 parts of zinc stearate (particle size 3μm); 8 parts of magnesium hydroxide (particle size 2μm); 2 parts of fluorescent tracer rhodamine B (purity 98%).

[0072] The production steps are as follows: S100: Mix the raw materials at 65°C and 650 rpm for 15 minutes to obtain a premix.

[0073] S200: adding reinforcing fibers, 450 rpm, 8 minutes.

[0074] S300: Multi-stage gradient blending: Low temperature and low speed: 105°C, 150 rpm, 6 minutes; Medium temperature and medium speed: 145°C, 300 rpm, 10 minutes; High temperature and high speed, 185℃, 450 rpm, 4 minutes, to make composite materials.

[0075] S400: Twin-screw extrusion granulation, 180℃, 250 rpm, cooling and pelletizing in a 25℃ water tank, particle size 4mm.

[0076] S500: Coated copper conductor, 200°C, 15 MPa, pulling 8 m / min, air cooling 20°C, winding 80N.

[0077] After testing, its tensile strength reaches more than 470MPa, and it can withstand a tensile force of 5400N without breaking in a simulated oil extraction tensile test.

[0078] Table 1 According to the comparison between Comparative Example 1 and Examples 1-3 in Table 1, it can be seen that the cable materials using bio-based polymer matrices have shown significant advantages. These materials are not only renewable and environmentally friendly, significantly reducing dependence on non-renewable resources, but also reducing carbon emissions during the production process. The combination of bio-based polymer matrices such as polylactic acid and polyhydroxyalkanoates can optimize the performance of cable materials and balance mechanical properties and processing properties. By adjusting the ratio and molecular weight of the two materials, the strength and toughness of the material can be improved, the processing fluidity can be improved, and the rigidity, biodegradability and biocompatibility of the material can be enhanced to adapt to different oil extraction environment requirements.

[0079] According to the comparison between Comparative Example 1 and Examples 4-6 in Table 1, it can be seen that the cable material composed of reinforced fibers exhibits significant performance advantages. Carbon fiber, due to its high strength and high modulus characteristics, significantly improves the tensile strength and rigidity of the cable, making it less likely to deform or break when subjected to large tensile forces, especially in environments such as the deep sea where the tensile strength of the cable is extremely high. The high temperature resistance and cut resistance of aramid fiber help the cable maintain structural integrity in high temperature environments and resist possible mechanical wear underground, ensuring the long-term stable operation of the cable. The chemical corrosion resistance of basalt fiber enables it to effectively protect the internal structure of the cable in a highly corrosive medium environment and prevent performance degradation due to corrosion. Natural fibers such as flax fiber, due to their wide sources, renewable nature and relatively low cost, improve the strength and toughness of the material and reduce the material cost to a certain extent. By reasonably adjusting the types and proportions of different reinforcing fibers, the performance of the cable can be customized according to the specific requirements of the oil production environment, so that the cable can work reliably under various complex and harsh oil production conditions.

[0080] In summary, the oil extraction tensile cable based on polymer materials of the present invention shows significant advantages in many aspects. In terms of bio-based polymer matrix, by flexibly adjusting the ratio and molecular weight of polylactic acid and polyhydroxyalkanoate, the mechanical properties, processing properties, biodegradability and biocompatibility can be accurately balanced to adapt to different mining environment requirements. Its renewability reduces resource dependence and carbon emissions, and it has good stability under harsh conditions. The diversified combination and proportion of reinforcing fibers have significant effects. Carbon fibers improve tensile strength and rigidity, aramid fibers ensure high-temperature wear resistance, basalt fibers resist chemical corrosion, and natural fibers enhance interaction, impart biodegradability and reduce costs. Overall, the cable of the present invention can operate reliably in different oil extraction scenarios, effectively solving many problems faced by traditional cables, and has excellent high temperature resistance, high pressure resistance, corrosion resistance, tensile strength, environmental protection and easy detection and maintenance.

[0081] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.

Claims

1. A polymer material-based oil production tensile cable, characterized in that: The cable comprises a conductor and an insulating layer coated on the outside of the conductor, wherein the insulating layer is made of a bio-based polymer composite material, and the bio-based polymer composite material comprises, by weight: 50-70 parts of a bio-based polymer matrix, 20-30 parts of reinforcing fibers, 3-5 parts of an antioxidant, 2-3 parts of a lubricant, 5-10 parts of a flame retardant, and 1-3 parts of a fluorescent tracer; The bio-based polymer matrix is ​​polylactic acid and polyhydroxyalkanoate; The reinforcing fibers include carbon fibers, aramid fibers, basalt fibers and natural fibers; The antioxidant is antioxidant 1010, with an active ingredient content of ≥98% or triphenyl phosphite, with a purity of 95%-99%; The lubricant is zinc stearate with a particle size of 2-5 μm or polyethylene wax with a molecular weight of 3000-6000; The flame retardant is magnesium hydroxide with a particle size of 1-3 μm, aluminum hydroxide with a particle size of 2-4 μm or tricresyl phosphate with a purity of 90%-95%; The fluorescent tracer is an organic or inorganic compound with fluorescent properties and compatible with a bio-based polymer matrix. The organic compound is rhodamine or coumarin, and the inorganic compound is europium-doped strontium aluminate.

2. The oil production tensile cable based on polymer materials according to claim 1 is characterized in that: The weight average molecular weight of the polylactic acid in the bio-based polymer matrix is ​​100,000-200,000, the weight average molecular weight of the polyhydroxyalkanoate is 80,000-150,000, and the mass ratio of the polylactic acid to the polyhydroxyalkanoate is 3:2-2:

1.

3. The oil production tensile cable based on polymer materials according to claim 1 is characterized in that: The carbon fiber in the reinforcing fiber has a diameter of 5-10 μm, a length of 3-8 mm, a tensile strength of 3000-5000 MPa, and an elastic modulus of 200-400 GPa; the aramid fiber has a diameter of 10-15 μm, a length of 2-6 mm, and a tensile strength of 2500-4000 MPa; the basalt fiber has a diameter of 8-12 μm, a length of 3-7 mm, and a tensile strength of 2000-3500 MPa.

4. The oil production tensile cable based on polymer materials according to claim 1, characterized in that: The natural fibers in the reinforcing fibers are flax fibers and sisal fibers, which account for 20%-40% of the total reinforcing fibers.

5. The oil production tensile cable based on polymer materials according to claim 1, characterized in that: The rhodamine in the fluorescent tracer has a purity of 95%-99%, the coumarin 343 has a purity of 90%-98%, and the europium-doped strontium aluminate has a particle size of 5-10 μm.

6. A method for producing a tensile cable for oil production based on polymer materials, characterized in that: The specific steps of the production method are: S100, raw material preparation and preliminary mixing: weigh the raw materials according to the weight ratio of the oil extraction tensile cable based on polymer materials according to claims 1-5 above, add the bio-based polymer matrix, antioxidant, lubricant, flame retardant and fluorescent tracer into a high-speed mixer, mix at 50-80° C. and a rotation speed of 500-800 rpm for 10-20 minutes to obtain a premix; S200, reinforcing fiber addition and mixing: adding reinforcing fiber to the premix, mixing in a high-speed mixer for 5-10 minutes, and adjusting the mixer speed to 300-600 rpm; S300, multi-stage gradient blending: The mixed materials are treated with a multi-stage gradient blending process, with preliminary mixing at a low temperature and low speed stage, gradual mixing of the premix core and the remaining polymer materials at a medium temperature and medium speed stage and diffusion outward, and strong mixing at a high temperature and high speed stage to obtain the treated bio-based polymer composite material; S400, twin-screw extrusion granulation: add the treated bio-based polymer composite material into the twin-screw extruder, set the screw temperature to 150-200℃, the screw speed to 200-300 rpm, and the extruded material is cooled in a water tank with the water temperature controlled at 20-30℃. After cooling, it is cut into pellets with a particle size of 3-5mm by a pelletizer; S500, cable coating molding: The bio-based polymer composite material pellets are coated on the conductor through an extruder, the extrusion temperature is 180-220℃, the extrusion pressure is 10-20MPa, and after traction, cooling and winding, the oil extraction tensile cable is obtained.

7. A method for producing a tensile cable for oil production based on polymer materials according to claim 6, characterized in that: In the S300, the temperature of the low-temperature and low-speed stage in the multi-stage gradient blending is set to 80-120° C., the rotation speed is 100-200 rpm, and the mixing time is 5-8 minutes.

8. The method for producing a tensile cable for oil production based on polymer materials according to claim 6, characterized in that: In the S300, the temperature of the medium-temperature and medium-speed stage in the multi-stage gradient blending is set to 130-160° C., the rotation speed is 250-350 rpm, and the time is 8-12 minutes.

9. The method for producing a tensile cable for oil production based on polymer materials according to claim 6, characterized in that: In the S300, the high temperature and high speed stage in the multi-stage gradient blending is set at a temperature of 170-200° C., a rotation speed of 400-500 rpm, and a time of 3-5 minutes.

10. The method for producing a tensile cable for oil production based on polymer materials according to claim 6, characterized in that: For the S500, the pulling speed in cable sheathing is set to 5-10 m / min, air cooling is adopted for cooling, the air temperature is 15-25° C., and the winding tension is controlled at 50-100N.

Citation Information

Cited By

  • Bio-based degradable cable material and preparation method thereof

    CN120944318A

  • A biobased degradable cable compound and a preparation method thereof

    CN120944318B

  • Composite material formed by degradable polyhydroxyalkanoate and fiber material and preparation method thereof

    CN122481324A